Allergen Induced Increase in Nonallergic Airway Responsiveness: A Citation Classic Revisited - Donald W Cockcroft (Canadian Respiratory Journal)
BACKGROUND:The present paper revisits the 1977 paper by DW Cockcroft, RE Ruffin, the late J Dolovich and FE Hargreave entitled "Allergen-induced increase in nonallergic bronchial reactivity" (Clin Allergy 1977;7:503-13) that became a citation classic. Although clinical types of asthma were recognized at the time, there was a poor understanding regarding the role of allergic reactions in causing increases in airway hyperresponsiveness. The objective was to study formally Dr Altounyan's observation that patients with asthma showed increases in airway responsiveness at the times of natural allergen exposure during pollen season. Thirteen atopic patients with asthma were studied over two days, following inhalation of diluent (control) and following doubling amounts of an allergen solution at 10-min intervals until forced expiration volume in 1 s fell by 20%. Methacholine and histamine challenges were performed before, at 8 h, at 32 h and seven days following the inhalations. A significant reduction (reduction of at least one doubling concentration) in the provocative concentration that causes a 20% fall in forced expiration volume in 1 s occurred in seven of 13 patients, and more often in subjects with a late bronchoconstrictor response to allergen challenge.